2014
DOI: 10.1590/s1519-38292014000300003
|View full text |Cite
|
Sign up to set email alerts
|

Assistência à criança: preenchimento da caderneta de saúde em municípios do semiárido brasileiro

Abstract: Objetivos: determinar a proporção de crianças com cadernetas de saúde com preenchimento adequado e analisar associações com características geográficas, socioeconômicas e biológicas maternas e da criança e com o percentual de utilização de serviços de saúde em dois municípios do semi-árido brasileiro. Métodos: estudo transversal de base populacional com crianças até cinco anos de idade. A coleta de dados foi realizada mediante aplicação de questionários domiciliar entre julho e setembro de 2008. A presença de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
25

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 16 publications
1
25
1
25
Order By: Relevance
“…Data on child monitoring are items to be completed by the health professionals in the healthcare services frequented by the child 5 . The CHR has been assessed since its implementation, with a predominance of cross-sectional studies seeking to quantify the frequency of entries recorded in the CHR, by means of direct observation of the record per se [7][8][9][10][11][12] . Some studies, adopting an analytical approach, evaluated the quality of the entries recorded as a dependent variable 6,7,9,11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on child monitoring are items to be completed by the health professionals in the healthcare services frequented by the child 5 . The CHR has been assessed since its implementation, with a predominance of cross-sectional studies seeking to quantify the frequency of entries recorded in the CHR, by means of direct observation of the record per se [7][8][9][10][11][12] . Some studies, adopting an analytical approach, evaluated the quality of the entries recorded as a dependent variable 6,7,9,11 .…”
Section: Introductionmentioning
confidence: 99%
“…The CHR has been assessed since its implementation, with a predominance of cross-sectional studies seeking to quantify the frequency of entries recorded in the CHR, by means of direct observation of the record per se [7][8][9][10][11][12] . Some studies, adopting an analytical approach, evaluated the quality of the entries recorded as a dependent variable 6,7,9,11 . In these studies, this variable was defined by the minimum percentage of entries duly filled out that are considered essential for monitoring child development 7 , the joint completion of all the information relating to the identification, growth, development and vaccination 9 or adequate recording of the growth and development curve 6,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figueiras et al 18 observed that 23.7% of charts were blank and only 15.6% of them were filled out completely in Belém. A study conducted in two municipalities of Piauí also showed a low percentage (22.2%) of adequately completed handbooks 10 . Unsatisfactory results were shown in Southeastern Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, a survey carried out by Vieira et al 9 in the city of Feira de Santana showed that, of the 2,319 CHHs evaluated, 39.6% of development curves were not adequately completed. A survey conducted in two municipalities of the Brazilian semi-arid region, in 2008, also found a low percentage of CHH completion 10 . Other countries, like Canada, use CHH-like instruments to monitor GD of children under five and implement WHO curves 11 .…”
Section: Introductionmentioning
confidence: 99%